PROPUESTA DE UN PLÁN DE MARKETING PARA LOS ATRACTIVOS NATURALES Y CULTURALES DE LA PARROQUIA ZUMBI, CANTÓN CENTINELA DEL CÓNDOR, PROVINCIA ZAMORA CHINCHIPE - Capa Ramón, Verónica Paulina (2016)
Tourism as a development generating activity is currently one the most important economic areas of revenue globally. In this regard, efforts to position destinations must be increasingly higher in order to locate the tourist activity in a place of importance and interest. In this context, the following research work that took place in the parish of Zumbi was the creation of a Marketing Plan in order to contribute to the development of tourism and socio-economic sector, and at the same time, enhance the parish as a tourist destination. The realization of this project served to have a clear direction of the potential that each of the attractions, and find the right tools that facilitate its dissemination, doing see the importance of a Marketing plan that allows to obtain an overview, for a possible local development integrating natural and cultural resources along with the human capital for the correct use of the same This project enabled a different perspective of the tourist activity. After that was the social, cultural, economic and tourist reality of the country and Zumbi parish, considered that it should contribute to the professional contribution and provide a possible solution to the different problems presented by the tourism field, therefore the need to consider the following research work was: "proposal of a PLAN of MARKETING tourist for the attractive natural and cultural of the parish ZUMBI ", CANTON sentry from the CONDOR, province ZAMORA CHINCHIPE." whose purpose was to publicize the tourism potential that has the parish. Based on the detailed above, the development of this research was raised as a general objective of the project: "Developing a marketing plan for the natural and cultural attractions, thus contributing to the socio-economic and touristic development of the parish Zumbi, canton sentry from the Condor, Zamora Chinchipe province", therefore intends to position the parish as one of the major tourist destinations in the South region , this raised three specific objectives: "A diagnosis of the current situation of the natural and cultural tourist attractions of the parish Zumbi, canton sentry from the Condor, Zamora Chinchipe province", through which was achieved through surveys, interviews, and visits to the site know the potentials and limiting current of the attractions of the parish. "Proposing a Marketing Plan, that allows to position it as a tourist destination in the province of Zamora Chinchipe", where through strategies of promotion and advertising became known the different natural and cultural attractions of the sector. Finally "socializing the proposed marketing plan with the atom decentralized government and community authorities in general parish Zumbi, canton sentry from the Condor, province Zamora Chinchipe.", it is effected by means of an exhibition in the municipality for the purpose of having knowledge of the work done and know its discretion against the proposal posed giving its conclusions and recommendations of the same. 5 Four methods that facilitated the gathering of information and the design of strategies and proposals were used during the development of the project, one of them was the deductive method to obtain relevant information from the cultural attractions to the approach of strategies, tactics, and goals that led to establishing the parameters required for the development of the marketing plan the inductive method was applied to analyze the information obtained from the survey and obtain conclusions in general. Another method was the descriptive allowing to describe the current reality of the cultural attractions to create their strengths, opportunities, weaknesses and threats. The historical method allowing to collect information and facts of the past in relation to the attractions, i.e. the historical review of the necessary references that allowed to understand the issues raised and propose strategies necessary for the development of the marketing plan. In addition to these methods a SWOT matrix was developed to raise key strengths, opportunities, weaknesses and threats of the attractions. As a result of the second specific objective, once collected information views and characteristics of the inhabitants of the place were to design the proposed marketing plan, raised strategic objectives; created material for advertising, promotion and dissemination: adhesives for buses, radio spots, social page, plan training, package tour, leaflets and information guide with the aim of using them as a tool to spread the tourist attractions of the parish Zumbi. In the proposal, was to meet one one the steps of a Strategic Plan, which were the result of the analysis of the current situation, determination of objectives, development and selection of tactics for the strategic plan. The conclusions that were raised at the end of this work were aimed mainly at the autonomous Government decentralized Canton sentry from the Condor, which is the body responsible for ensuring the tourist resource in the area of study and who can take leadership and execution of programmes and projects described in this research work, taking advantage of the increased positioning socio-political Governments today self-employed since only in this way can generate a more active participation and empowerment of citizens around the tourist issue. The recommendations will spell out recommendations that will favor in the search for alternatives that contribute to the promotion of the place; and finally enclosed several annexes which consist of photographs, cards, documents, etc which shows the work done.